Self-powered, frequency selective resonator array type artificial basilar membrane for the totally implanted cochlear implant - Kang, Tae-Uk; Park, Youngjin; Song, Sangmin; Park, No-Cheol; Jeon, Hojeong; Park, Jin-Woo (Elsevier BV, 2025)
The human auditory system can sensitively detect sounds over a wide frequency range from 20 Hz to 20,000 Hz. This capability is attributed to the multi-resonance characteristics of the basilar membrane in the inner ear, which enables frequency selectivity by responding to different frequencies at different positions. Sensorineural hearing loss is a condition in which sound stimuli fail to be converted into neural signals due to inner ear damage. Although cochlear implants (CIs) can address this condition, issues related to the external components and battery dependency of CIs are still challenging. Artificial basilar membranes that mimic the human auditory system achieve frequency selectivity using a trapezoidal membrane, similar to the actual basilar membrane. However, this approach results in sensitivity loss due to different active areas for different frequencies and challenges in miniaturization. In this study, frequency selectivity was achieved in the range from 570 Hz to 8010 Hz while maintaining the constant active area within the frequency bandwidth by adjusting the mass and the spring constant. To enable self-powered operation, fluorinated ethylene propylene was used as the electret material, and the surface potential was enhanced through microstructural control via sintering. With a total of nine channels with total sensing area of 15 x 15 mm2, a compact artificial basilar membrane was implemented. The proposed miniaturized artificial basilar membrane is expected to contribute to the realization of artificial auditory systems.